2022
DOI: 10.3332/ecancer.2022.1343
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice regarding the behavioural risks of cancer among college students in Ethiopia

Abstract: In recent years, morbidity and mortality due to cancer has been increasing in Ethiopia, putting it among the most important public health issues. Cancer and associated complications can be prevented provided that effective interventions are put in place to control risk factors. Therefore, this study aimed to assess the level of knowledge and practice of preventable behavioural risk factors of cancer. We conducted a cross-sectional study among 200 college students in Northeast Ethiopia utilising quantitative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This study found level of knowledge about cancer and cancer prevention. Other studies in LMICs showed poor levels of public knowledge about cancer symptoms (67.6%) in Saudi Arabia and behavioral risk factors (61%) in Ethiopia [25,26]. Similarly, another study in Turkey revealed that adult individuals had a significant level of false and incomplete information about cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…This study found level of knowledge about cancer and cancer prevention. Other studies in LMICs showed poor levels of public knowledge about cancer symptoms (67.6%) in Saudi Arabia and behavioral risk factors (61%) in Ethiopia [25,26]. Similarly, another study in Turkey revealed that adult individuals had a significant level of false and incomplete information about cancer [27].…”
Section: Discussionmentioning
confidence: 99%